EFEKTIFITAS METODE BIRTHING BALL TERHADAP PERCEPATAN PEMBUKAAN PADA IBU BERSALIN DI KLINIK KARTIKA HUSADA DONOMULYO - Astutik, Nina Andri; Retnaningsih, Reny; Sulistiyah (Fakultas Ilmu Kesehatan, 2025)
Prolonged labor is one of the causes of maternal death. Prolonged labor can cause bleeding, shock, and death in the mother and fetal distress, asphyxia, and caput. There are several physiological efforts that can be done to accelerate and facilitate cervical dilation such as sitting on a birth ball. The purpose of this study was to determine the effectiveness of the birthing ball method on accelerating cervix dilation at Klinik Kartika Husada, Donomulyo.MethodThis study uses a quantitative method, with a quasi-experimental design. This study uses a post-only control group design. In the intervention group, the study was given treatment using the birthing ball method, while in the control class, the birthing ball method was not given treatment. Determination of the number of respondents using a sampling technique, namely nonprobability sampling with a purposive sampling approach by considering the inclusion and exclusion criteria. The sample in this study was primigravida mothers who normally labor at Klinik Kartika Husada , a total of 13 primigravida mothers in the intervention group and 13 primigravida mothers in the control group. ResultsFrom the statistical analysis of the Mann-Whitney test with Î± = 0.05, the p value was obtained as 0.007 with p 0.000 < 0.05, so H0 was rejected, which means that the birthing ball method is effective in accelerating cervix dilation in primigravida at the Klinik Kartika Husada, Donomulyo. conclusionThere is an effectiveness of the birthing ball method in accelerating cervix dilation in primigravida at the Klinik Kartika Husada, Donomulyo